1999
DOI: 10.1083/jcb.147.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Rad51 and Dmc1 Form Mixed Complexes Associated with Mouse Meiotic Chromosome Cores and Synaptonemal Complexes

Abstract: The eukaryotic RecA homologues RAD51 and DMC1 function in homology recognition and formation of joint-molecule recombination intermediates during yeast meiosis. The precise immunolocalization of these two proteins on the meiotic chromosomes of plants and animals has been complicated by their high degree of identity at the amino acid level. With antibodies that have been immunodepleted of cross-reactive epitopes, we demonstrate that RAD51 and DMC1 have identical distribution patterns in extracts of mouse sperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
178
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(205 citation statements)
references
References 81 publications
(119 reference statements)
26
178
1
Order By: Relevance
“…These foci are thought to represent sites on chromatin where DNA repair reactions take place. Similarly, RAD51 forms foci on meiotic chromosomes, where it colocalizes with DMC1 (Barlow et al, 1997;Tarsounas et al, 1999). These foci appear similar to the RAD51 foci observed in somatic cells after DNA damage and presumably identify sites of meiotic recombination (Haaf et al, 1995;Raderschall et al, 1999).…”
Section: Predominant In G1supporting
confidence: 54%
“…These foci are thought to represent sites on chromatin where DNA repair reactions take place. Similarly, RAD51 forms foci on meiotic chromosomes, where it colocalizes with DMC1 (Barlow et al, 1997;Tarsounas et al, 1999). These foci appear similar to the RAD51 foci observed in somatic cells after DNA damage and presumably identify sites of meiotic recombination (Haaf et al, 1995;Raderschall et al, 1999).…”
Section: Predominant In G1supporting
confidence: 54%
“…This hypothesis is based on observations made in the electron microscope where LNs were seen in close contact to the CE of beetle spermatocytes (Schmekel and Daneholt 1998). Furthermore, the above described interactions between proteins of the homologous recombination machinery and SC components (Tarsounas et al 1999;Bolcun-Filas et al 2009) provide initial indications for a complex interaction network between the elements of these two meiotic features which might explain their tight interdependency. 2) Besides the reciprocal recombination of the DNA, the chromosomal axes also need to be exchanged to produce chiasmata.…”
Section: Third Step: the Mature Scmentioning
confidence: 95%
“…Besides, different studies have reported about interactions between early proteins of the recombination machinery and SC components. In the first study, binding abilities of the recombinases RAD51 and DMC1 with SYCP3 and between RAD51 and SYCP1 could be detected in a yeast two-hybrid system (Tarsounas et al 1999). Furthermore, Syce1 -/-spermatocytes revealed a co-localization of RAD51 and SYCE2.…”
Section: Second Step: the Assembly Of The Central Regionmentioning
confidence: 96%
See 2 more Smart Citations